Ansiedade infantil das crianças brasileiras um ano após a pandemia COVID-19 - Amorim, Tainara de Jesus [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The spread of Corona Virus Disease (COVID-19) infection requires continuous knowledge of its epidemiology. In Brazil, a pandemic greatly influenced children across the country and events such as the closing of schools affected the daily lives of families. The COVID-19 pandemic has led to isolation and social restrictions, which are relevant to children especially if they are not well understood and are frightened. The aim is to assess the prevalence of anxiety in Brazilian children aged 6 to 12 years and its associated factors one year after the onset of the COVID-19 pandemic. This is a cross-sectional study carried out between March and May 2021. Data collection was performed through an online questionnaire on the Google Forms platform, distributed through social networks (Twitter, Facebook, Instagram) and personal contacts (WhatsApp and email) that expands through a snowball across Brazil. Participants were children between 6 and 12 years old and their parents or guardians. This research was approved by the Research Ethics Committee of Brazil (CAAE: 30547320.0.0000.0008 and Opinion nº 4,128,847) and a new request and approval was granted for data collection one year after the pandemic (Opinion nº 4,593,273). The Child Anxiety Questionnaire (CAQ) and the Numerical Rating Scale (NRS) were used to measure anxiety. Of the 906 children, 53.3% (n = 483) are girls, the average age of 8.79 ± 2.05 years, 87.1% (n = 789) of respondents are mothers, with 70.9% (n = 642) participants from the Southeast. Based on a CAQ ≥ 9, the prevalence of anxiety was 24.9% (n = 226). In logistic regression, the following variables were associated with higher CAQ scores: children's age and the child having a chronic disease or disability. Based on NRS ≥ 7, the prevalence of anxiety was 34.8% (n = 315). In logistic regression, the following variables were associated with the highest in the NRS: the child having a chronic disease or disability, children's understanding of the pandemic (much or nothing), decreased family income, region of the country (southeast, midwest and north), the age of the guardians and the instrument being answered by the mothers, grandmothers or other family members. The prevalence of anxiety among children after one year of the COVID-19 pandemic was 24.9% (n = 226) according to the CAQ and 34.8% (n = 315) according to the NRS. These results are higher than the prevalence reported for children at the beginning of the pandemic, which was 19.4% (n = 56), according to the CAQ, and 21.8% (n = 63), according to the NRS. Higher levels of anxiety were associated with the child having a chronic illness or disability in both instruments used. These findings reveal the need to implement public health actions aimed at these parents and children at the population level. This study contributes to characterize the evolution of the pandemic in Brazil, providing a basis for making comparisons with the literature and other countries.

A disseminação da infecção da Corona Virus Disease (COVID-19) requer um conhecimento contínuo sobre sua epidemiologia. No Brasil, a pandemia COVID-19 influenciou o cotidiano das crianças e das famílias em especial pelo fechamento de escolas por um longo período. A pandemia COVID-19 levou a isolamento e restrições sociais que são significativamente relevantes para as crianças, especialmente se elas não são bem compreendidas e mostram-se amedrontadas. O objetivo é avaliar a prevalência de ansiedade das crianças brasileiras de 6 a 12 anos e seus fatores associados um ano após o início da pandemia COVID-19. Trata-se de um estudo transversal realizado entre os meses de Março e Maio de 2021. A coleta de dados foi realizada por meio de um questionário on-line na plataforma Google Forms, distribuído pelas redes sociais (Twitter, Facebook, Instagram) e contatos pessoais dos autores (WhatsApp e e-mail) que se expandiram por meio de uma bola de neve em todo o Brasil. Os participantes foram crianças entre 6 e 12 anos e seus pais ou responsáveis. Esta pesquisa foi aprovada pelo Comitê de Ética em Pesquisa do Brasil (CAAE: 30547320.0.0000.0008 e Parecer nº 4.128.847) e uma nova solicitação e aprovação foi concedida para a coleta de dados um ano após a pandemia (Parecer nº 4.593.273). O Children´s Anxiety Questionnaire (CAQ) e o Numerical Rating Scale (NRS) foram utilizados para medir a ansiedade. Das 906 crianças, 53,3% (n = 483) são meninas, a média de idade de 8,79 ± 2,05 anos, 87,1% (n = 789) dos entrevistados são mães, com 70,9% (n = 642) participantes do Sudeste. Com base no CAQ ≥ 9, a prevalência de ansiedade foi de 24,9% (n = 226). Na regressão logística, as seguintes variáveis estiveram associadas aos maiores escores do CAQ: idade das crianças e a criança ter doença crônica ou deficiência. Com base na NRS ≥ 7, a prevalência de ansiedade foi de 34,8% (n = 315). Na regressão logística, as seguintes variáveis foram associadas a maiores escores do NRS: a criança ter doença crônica ou deficiência, compreensão das crianças sobre a pandemia (muito ou nada), diminuição da renda familiar, região do país (sudeste, centro-oeste e norte), a idade dos responsáveis e o instrumento ser respondido pelas mães, avós ou outros membros da família. A prevalência de ansiedade entre as crianças após um ano pandemia COVID-19 foi de 24,9% (n = 226), segundo CAQ, e 34,8% (n = 315), segundo o NRS. Esses resultados são superiores à prevalência relatada para crianças no início da pandemia que foi de 19,4% (n = 56), segundo o CAQ, e 21,8% (n = 63), segundo o NRS. Níveis mais elevados de ansiedade foram associados ao fato da criança ter uma doença crônica ou deficiência em ambos os instrumentos utilizados. Esses achados sugerem a necessidade de implementação de ações de saúde pública direcionadas a esses pais e filhos em nível populacional. Este estudo contribui para caracterizar a evolução da pandemia no Brasil, produzindo uma base para fazer comparações com a literatura e com outros países.
Childhood anxiety in Brazilian children one year after the COVID-19 pandemic
Keywords: Anxiety; Kids; Pandemic; Pediatric nurse; Pediatria; Pesquisa em enfermagem; Enfermagem pediátrica; Ansiedade; Crianças; COVID-19; Pandemias